IMPLEMENTASI METODE SNOWBALL THROWING UNTUK MENINGKATKAN MINAT DAN AKTIVITAS BELAJAR EKONOMI - Fitri Nurlaili; Dewi Sulastri (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
This research was a classroom action research that aim to increase the interest and learning activities of economic lesson at the second grade of social science in Al-munawwaroh Senior High School Cilegon through implementation of snowball throwing method. This research was conducted in a collaborative and participatory in two cycles. Data collection in this research conducted with observation, questionaire and documentation. Data analysis performed was quantitative data analysis using percentage that conducted by describing the obtained quantitative data presented in the form of tables then made conclusions. Based on the research concluded that implementation of snowball throwing could increase interest and learning activity of economic lesson. The evidences were showed by improving in indicator of interest in economic lesson and learning activity. In cycle one the average score was 69,46% and in cycle two was 80,78%; there were 11.32 % improvement. Score of learning activity of economic lesson in cycle one was 73,62% and in cycle two was 85,65%; the improvement of learning activity of economic lesson was 12,03%.